Embedded systems hardware for software engineers - Lipiansky, Ed (McGraw-Hill Companies, 2012)
"'Embedded Systems Hardware for Software Engineers' describes the electrical and electronic circuits that are used in embedded systems, their function, and how they can be interfaced to other devices." -- P.4 of cover.